Pengaruh Religiusitas dan Pengetahuan Etika Bisnis Islam terhadap Perilaku Bisnis Pedagang Muslim di Pasar Merdeka Samarinda - Amanda Azwar Azhari; Rinna Ramadhan Ain Fitriah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study is motivated by the persistence of trading practices that are not fully aligned with sharia principles, such as dishonesty and unfairness in transactions. The objective of this research is to analyze the influence of religiosity and Islamic business ethics knowledge on the business behavior of Muslim traders at Pasar Merdeka Samarinda. This study employs a quantitative approach using a survey method. The population consists of all Muslim traders operating in the market, totaling 367 individuals. The sample comprises 79 respondents, determined using the Slovin formula with a purposive sampling technique. Data were collected through Likert-scale questionnaires and analyzed using ordinal logistic regression with the assistance of IBM SPSS Statistics 25. The results indicate that religiosity has a positive and significant effect on the business behavior of Muslim traders. In addition, knowledge of Islamic business ethics also has a positive and significant influence in shaping business behavior in accordance with sharia principles. Simultaneously, both variables play an important role in encouraging honest, trustworthy, responsible, and fair trading practices. Practically, this study implies that improving religiosity and understanding of Islamic business ethics are essential in promoting ethical trading practices in traditional markets. However, this study is limited by the relatively small sample size and its focus on a single location, thus limiting the generalizability of the findings to other contexts.